The Effect of Snake and Ladder Game Media on Knowledge of Oral Bad Habits Among Fifth-Grade Students at SDN 10, Padang - Zelin Jelita; Satria Yandi; Intan Batura Endo Mahata (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Oral bad habits are habits that occur in the oral cavity that can cause abnormal tooth growth and development. Dental and oral health education is the first step in increasing children's knowledge and awareness of maintaining dental and oral health. The educational game of Snakes and Ladders can help children more easily understand and comprehend the knowledge they have acquired in an interesting way. Materials and Methods: This study is a pre-experimental study using a one-group pretest-posttest design with simple random sampling. Data collection was conducted by administering a questionnaire while playing the Snakes and Ladders game to fifth-grade students at SDN 10 Sungai Sapih Padang with four interventions. Results and Discussion: The sample size in this study was 21 students. The results showed that the average knowledge of students increased from 30% to 100% after the educational Snakes and Ladders game intervention. Conclusion: From the research results, it can be concluded that the use of the educational snake and ladder game can influence knowledge about oral bad habits among fifth-grade students at SDN 10 Sungai Sapih Padang (p=0.000).